THE PERSON’S HEALTH AS A PHILOSOPHICAL AND RELIGIOUS PROBLEM - Степанюк, Ю. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to analyze the main aspects of the such problem as the health of man, it’s philosophical and religious content.